Perspektif Baru tentang Kematian Singamangaraja - Kozok, Uli (Lembaran Sejarah, 2024)
Ompu Pulo Batu, the last Singamangaraja, died on 17 June 1907, in the Kalasan area of Humbang-Hasundutan Regency, North Sumatra. After being pursued for several weeks by counter-guerrilla forces led by Captain Hans Christoffel, he was ambushed along with his family and a few of his followers. The exact circumstances of his death remain uncertain, leading to several conflicting accounts. In this paper, the existing sources are re-evaluated to provide a clearer understanding of the death of the last Batak priest-king. From the available sources, including archival data, it is also revealed that the prevailing theories about who killed Singamangaraja are incorrect.